1982
DOI: 10.2134/jeq1982.00472425001100030035x
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture and Water Quality in the Canadian Great Lakes Basin: V. Pesticide Use in 11 Agricultural Watersheds and Presence in Stream Water, 1975–1977

Abstract: A survey of 11 agricultural watersheds located in southern Ontario revealed 81 pesticides were applied on farms and rights‐of‐way during 1975. An average of 39% of the land surface in the 11 watersheds was treated with a mean rate of 8.27 kg ha−1 of fungicides, herbicides, insecticides, and nematocides. This was equivalent to an average of 3.25 kg ha−1 year−1 over the whole area, with application rates varying from 0.005 kg ha−1 on hay and pasture to 51 kg ha−1 on potatoes (Solanum tuberosum L.), tomatoes (Lyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 0 publications
3
31
0
1
Order By: Relevance
“…Endosulfan has a half life of 60-800 days in soil (ATSDR 2000). Frank et al (1982) have also reported that because of its persistence in soil, endosulfan residues were detected in water samples throughout the year (outside the spray season) with storm runoff. The results of several laboratory and greenhouse studies indicate that α-and β-endosulfan are strongly adsorbed to soil (Bowman et al 1965;El Beit et al 1981a, 1981b.…”
Section: Discussionmentioning
confidence: 98%
“…Endosulfan has a half life of 60-800 days in soil (ATSDR 2000). Frank et al (1982) have also reported that because of its persistence in soil, endosulfan residues were detected in water samples throughout the year (outside the spray season) with storm runoff. The results of several laboratory and greenhouse studies indicate that α-and β-endosulfan are strongly adsorbed to soil (Bowman et al 1965;El Beit et al 1981a, 1981b.…”
Section: Discussionmentioning
confidence: 98%
“…The multiple-year data sets for the LAPU in various watersheds come from the NASQAN and NAWQA programs and from the literature (11,14,27,31,(39)(40)(41)(42)(43). The yearto-year variability in LAPU can be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Due to constant leaching as well as superficial runoff during rainfall and to accidental spillage, endosulfan has repeatedly been reported in surface waters of developing and developed countries (Herzel 1972, Van Dyk & Greeff 1977, Wall et al 1978, Frank et al 1982, Baier et al 1985. In the Dutch section of the river Rhine, mean concentrations of 0.1 to 0.3 pg 1-', with maximum values of 0.81 pg 1-' in 1969 and since then decreasing, have been reported for the period 1969 to 1975 (Wegmann & Greve 1978).…”
Section: Introductionmentioning
confidence: 99%